Quantal Release of Dopamine and Action Potential Firing Detected in Midbrain Neurons by Multifunctional Diamond-Based Microarrays - Tomagra, Giulia; Picollo, Federico; Battiato, Alfio; Picconi, Barbara; De Marchis, Silvia; Pasquarelli, Alberto; Olivero, Paolo; Marcantoni, Andrea; Calabresi, Paolo; Carbone, Emilio; Carabelli, Valentina (Frontiers in Neuroscience, 2019)
Micro-Graphitic Single Crystal Diamond Multi Electrode Arrays (µG-SCD-MEAs) have been used so far as amperometric sensors for detecting catecholamines from chromaffin cells or adrenal gland slices. Besides having time resolution and sensitivity comparable with carbon fiber electrodes (CFEs), that represent the gold standard for amperometry, μG-SCD-MEAs have also the advantages of simultaneous multisite detection, high biocompatibility and implementation of amperometric/potentiometric protocols, aimed at monitoring exocytotic events and neuronal excitability. To adapt diamond technology to record neuronal activity, in this work µG-SCD-MEAs have been interfaced with cultured midbrain neurons, to detect electrical activity as well as quantal release of dopamine (DA). µG-SCD-MEAs are based on graphitic sensing electrodes embedded into the diamond matrix and are fabricated by MeV ion beam lithography. Two geometries have been adopted, with 4×4 and 8×8 microelectrodes (20×3.5 μm2 exposed area, 200 μm spacing). In the amperometric configuration, the 4×4 μG-SCD-MEAs resolved quantal exocytosis from midbrain dopaminergic neurons. KCl-stimulated DA release occurred at a mean frequency of 0.4 Hz, as amperometric spikes of 15 pA amplitude and 0.5 ms half-width. When used as potentiometric multiarrays, the 8×8 μG-SCD-MEAs detected the spontaneous spiking activity of midbrain neurons. Extracellularly recorded action potentials (APs) had mean amplitude of ~ -50 μV and occurred at a mean firing frequency of 0.7 Hz for most neurons (67%), while the remaining fired at 6.8 Hz. Comparable findings were observed using conventional MEAs (0.9 Hz and 6.4 Hz, respectively). To test the reliability of potentiometric recordings with μG-SCD-MEAs, the D2-autoreceptor modulation of firing was investigated by applying levodopa (L-DOPA, 20 μM), and comparing μG-SCD-MEAs, conventional MEAs and current-clamp recordings. In all cases, L-DOPA reduced by 70% the spontaneous spiking activity in most neurons, while the D2-antagonist sulpiride reversed this effect. Cell firing inhibition was generally associated with increased APs amplitude. A minority of neurons was either insensitive or potentiated by L-DOPA, suggesting that AP recordings originate from different midbrain neuronal subpopulations and reveal different modulatory pathways. Our data demonstrate, for the first time, that µG-SCD-MEAs are multi-functional biosensors suitable to resolve real-time DA release and AP firing from in vitro neuronal networks.